Characteristics of medication-induced xerostomia and effect of treatment. - Kayoko Ito; Naoko Izumi; Saori Funayama; Kaname Nohno; Kouji Katsura; Noboru Kaneko; Makoto Inoue (PLoS ONE, 2023)
Objective Side-effects of medications cause xerostomia. There have been cases where a medication has been discontinued owing to its severe side-effects. Therefore, the xerostomia must be treated to ensure that the primary disease is managed effectively. This study analyzed the actual status of patients with medication-induced xerostomia and investigates factors associated with its improvement. Methods This study assessed 490 patients diagnosed with medication-induced xerostomia who had an unstimulated salivary flow of ≤0.1 mL/min and received treatment for xerostomia at a xerostomia clinic. Patient age, sex, medical history, medications used, disease duration of xerostomia, and psychological disorders were recorded. The anticholinergic burden was assessed using the Anticholinergic Cognitive Burden scale. The unstimulated salivary flow was measured by the spitting method. According to their symptoms and diagnoses, the patients were introduced to oral lubricants, instructed on how to perform massage, and prescribed Japanese herbal medicines, and sialogogues. Factors associated with the subjective improvement of xerostomia and objective changes in the salivary flow rate were recorded at six months. Results Xerostomia improved in 338 patients (75.3%). The improvement rate was significantly lower in patients with psychiatric disorders (63.6%) (P = 0.009). The improvement rate decreased as more anticholinergics were used (P = 0.018). However, xerostomia improved in approximately 60% of patients receiving three or more anticholinergics. The unstimulated salivary flow increased significantly more in patients who reported an improvement of xerostomia (0.033±0.053 mL/min) than in those who reported no improvement (0.013±0.02 mL/min) (P = 0.025). Conclusion Xerostomia treatment improved oral dryness in 75.3% of patients receiving xerogenic medications in this study. If xerostomia due to side-effects of medications can be improved by treatment, it will greatly contribute to the quality of life of patients with xerogenic medications and may reduce the number of patients who discontinue medications.